A relativização da coisa julgada nas ações coletivas - Souza, Dairson Mendes de (2005)
This paper deals with the polemic subject of the relativization of the thing adjudged focusing on the collective actions. By the beginning it seems to be necessary to delimitate the issue of this study. There are collective actions applied to concrete cases and collective actions that deal with the abstract control of constitutionality. In the present work we have studied the collective actions applied to concrete cases. But not all kinds of collective actions in this category have been analysed though, because some of them are too specific and writing about them would take a deepness and extension not intended for this study. We didn t consider the collective actions that deal with the abstract control of constitutionality either because the relativization of the thing adjudged does not apply to them. Before facing the main subject we decided to make some considerations about jurisdiction, sentences, thing adjudged, collective actions, nullities that affect the sentences, thing adjudged and litispendency in the collective actions. Then we came to the main subject of this work and developed an argumentation to try to find a solution for the difficult balance: legal security versus justice in the judicial decisions. By the end we present a suggestion for the relativization of the thing adjudged in the collective actions applied to concrete cases